Quality and Relevance of Domain-specific Search: A Case Study in Mental Health - Tang, Thanh; Craswell, Nick; Hawking, David; Griffiths, Kathleen; Christensen, Helen (Information Retrieval, 2006)
When searching for health information, results quality can be judged against available scientific evidence: Do search engines return advice consistent with evidence based medicine? We compared the performance of domain-specific health and depression search engines against a general-purpose engine (Google) on both relevance of results and quality of advice. Over 101 queries, to which the term ’depression’ was added if not already present, Google returned more relevant results than those of the domain-specific engines. However, over the 50 treatment-related queries, Google returned 70 pages recommending for or against a well studied treatment, of which 19 strongly disagreed with the scientific evidence. A domain-specific index of 4 sites selected by domain experts was only wrong in 5 of 50 recommendations. Analysis suggests a tension between relevance and quality. Indexing more pages can give a greater number of relevant results, but selective inclusion can give better quality.
://research.microsoft.com/users/nickcr/pubs/tang_ir06.pdf